Given the following equation:
![(x)/(x-4)-(4)/(x)=(3)/(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/z1ebp9vboengg9e0niesarqf5x51zz0uk3.png)
First, we will identify the zeros of the denominator
So, the zeros are: x = {0,4}
Second, multiply the equation by x(x-4) to eliminate the denominators
![x(x-4)*((x)/(x-4)-(4)/(x))=x(x-4)*(3)/(x-4)](https://img.qammunity.org/2023/formulas/mathematics/college/j1omimb2qab3jgcd93sjdqf3it3056kdzh.png)
Simplify the equation:
![x^2-4(x-4)=3x](https://img.qammunity.org/2023/formulas/mathematics/college/1o4wtzx01qeg635rgcsv5fj13svqbofsz7.png)
Expand the equation and combine the like terms:
![\begin{gathered} x^2-4x+16=3x \\ x^2-7x+16=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/lijkrkn2zozcv7kwd8y5jvs2orra9wc0bd.png)
The last quadratic equation will be solved using the quadratic rule:
![x=(-b\pm√(b^2-4ac))/(2a)](https://img.qammunity.org/2023/formulas/mathematics/college/jr19ixi2zltkocy82qhxfiop5lyv4hzbkm.png)
Substitute a = 1, b = -7, c = 16
![\begin{gathered} x=(7\pm√((-7)^2-4(1)(16)))/(2(1)) \\ \\ x=(7\pm√(-15))/(2)=(7\pm i√(15))/(2) \\ \\ x=\lbrace(7+i√(15))/(2);(7-i√(15))/(2)\rbrace \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/47xoi4of1pgb87zya5fd8v973vdsct5w7w.png)
So, the answer will be:
![x=\lbrace(7+i√(15))/(2);(7-i√(15))/(2)\rbrace](https://img.qammunity.org/2023/formulas/mathematics/college/hjlstctu2xwspd7ur7e3rmm6uqxistzvwz.png)